Pengaruh Human Relation (Hubungan Antar Manusia) dan Kondisi Lingkungan Kerja Fisik Terhadap Etos Kerja Pegawai Pada PDAM Tirtanadi Sumatera Utara Cabang Cemara Medan - Sri Muliyani (Journal Economy and Currency Study (JECS), 2019)
This study aims to determine and explain the influence of Human Relation and Physical Working Condition Effect Of Work Ethic At PDAM Tirtanadi North Sumatra Branch of Cemara Medan. Research is done on PDAM Tirtanadi North Sumatra Branch of Cemara Medan. The population in this study as many as 32 people, while the sample is 32 people and used total sampling method. Techniques of data collection is used questionnaires, the questionnaires were distributed to respondents and then the respondents must be reconvence the questionnaires again. Data analysis technique is used multiple linear regression with the formula Y = a + b1 X1 + b2 X2+ b3 X3+e. Before data is processed by regression, the fisrt data must be compare with independent variable with multicollinearity test, heterokedesitas test, and autocoleration test. If we want to know the contribution of human relation factor, physical working condition and work ethic we must to used determinant formula (R2). After the questionnaires has been analyzed so we can get the multiple linear regression Y= 2,970+0,381X1+0,341X2 +e. And then we can get the determinant coefficient (R2) is 0,557 it mean human relation variable and physical working condition is 55,7 % and it more 44,3 % is depend on the other factor. From the Study above the real fact is the hypothesis can be received if tcount<ttable.Fom the study we can get that X1 (3,047) and X2 (4,057) > 2,04 or tcount>ttable, it mean that human relation and physical working condition has jointly significant effect on work ethic at PDAM Tirtanadi North Sumatra Branch of Cemara Medan. This study is used F test, it is doing for how far human relation, physical working condition has jointly significant effect on work ethic at PDAM Tirtanadi North Sumatra Branch of Cemara Medan.and it can be see by the value of Fcount(18,235) > Ftable (3,33).